„Obudź się więc i pracuj”. Nowe spojrzenie na „Parnas we śnie” Tymona Zaborowskiego - Dąbrowski, Roman (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
This article presents Tymon Zaborowski’s poem “Parnassus in a Dream” as serving primarily as a means of self-presentation and self-promotion for the young poet. Contrary to earlier opinions about this work, which by and large viewed it as an expression of the author’s aesthetic and literary beliefs, attention is drawn to its humorous nature. Examples of comic passages are shown, at times juxtaposed with “serious” fragments, thus highlighting the poet’s tendency to adopt an external perspective on his own ideas. The key issue here is the author's attitude toward the epic, a genre previously attempted, without much success, by Voltaire and Ignacy Krasicki, who acted as guides to the narrator’s dream of Parnassus. As the author of this article points out, Zaborowski himself announced at the end of the poem his intention to ascend the “epic mountain”.